BARTLEBY AND BENITO CERENO - HERMAN MELVILLE (NEW YORK DOVER PUBLICATIONS, 1990)
. "Bartleby" is an intriguing moral allegory set in the business world of mid-19th-century New York. A strange, enigmatic man employed as a clerk in a legal office, Bartleby forces his employer to come to grips with the most basic questions of human responsibility, and haunts the latter's conscience, even after Bartleby's dismissal. "Benito Cereno," considered one of Melville's best short stories, deals with a bloody slave revolt on a Spanish vessel. A splendid parable of man's struggle against the forces of evil, the carefully developed and mysteriously guarded plot builds to a dramatic climax while revealing the horror and depravity of which man is capable.
Keywords: English Short Stories